Outcomes of infants born to mothers receiving methadone for pain management in pregnancy. Issue 1 (1st January 2004) - Sharpe, C; Kuschel, C
Abstract : Objective: To assess the outcomes of infants born to mothers receiving methadone for the management of pain in pregnancy. Design: A retrospective audit was conducted of neonatal outcomes in 19 cases in which methadone was used in the management of maternal pain (pain group). Twenty four cases in which methadone was used for maintenance of opiate addiction in pregnancy served as a comparison group (maintenance group). Setting: Regional level 3 neonatal service. Results: Infants in the pain group were exposed to significantly smaller methadone doses, for shorter periods, starting later in pregnancy. Only 11% of them required treatment for neonatal abstinence syndrome, whereas 58% of infants in the maintenance group required treatment. Other neonatal morbidity in the pain group was considerable, probably related to prematurity. Infants in the pain group had significantly higher z scores for birth weight and head circumference, but not length, than the infants in the maintenance group. Conclusions: Methadone used for the treatment of maternal pain resulted in a low incidence of neonatal abstinence syndrome. Infants were normally grown. However, there was significant morbidity related to slight prematurity, and delivery in this group should be delayed until term if possible.